A brief introduction to the Matlab program - Tomozei, I.C; Axinte, T; Paraschiv, L (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The paper aims just a brief introduction to the MATLAB software. In this article, we study three cases: right triangle, pendulum and simply supported beam. In the first case, we make a right triangle that has the following dimensions: 3m, 4m and 5m. Moreover, in the second case, we calculate the angle αt from a simple pendulum. In the last case, is determined shear force and bending moment only when the uniform distributed load act on the simply supported beam (SSB).